Basic Concepts and Categories of Penitentiary Security Theory - DZHANSARAYEVA, Rima Yerenatovna; BAISALOV, Ali Dzhumamuratovich; MALIKOVA, Sholpan Baltabekovna; ATAKHANOVA, Gulzagira Makhatovna; KUSMAMBETOV, Kuanysh Daniyarovich (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
Provision of security of individuals, society and the state in modern conditions cannot be implemented without the legal regulation of social relations in order to prevent potential security threats and neutralize existing ones. Accordingly, the functioning of the legal system, its social role and functions are of great importance in terms of security. A special role in the sphere of legal security belongs to public authorities, ensuring the security of legal system. The necessity to build a legal and social, and most importantly – viable state objectively increases the importance of government activity and state bodies. Current state of the penal system, its reform processes within the framework of development and integration of the state into the world community leads to the emergence of new threats. In this regard, there becomes a need to increase its readiness to confront arising external and internal, real and potential threats affecting a particular entity and the general situation. Penitentiary security, on the one hand, is a security of the person, society and state within the penitentiary system, on the other hand, is a security of society and the state of internal penal hazards beyond the borders of a penitentiary system, the severity of which was not forewarned by internal prison security or caused by factors and subjects of the penitentiary system aimed against the legitimate penitentiary process within the system to its disorganization and replacement with illegal with harmful activity coming out of the system.